2020
DOI: 10.1002/lary.29342
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Multiple Tympanostomy Tube Placements in Children: Systematic Review and Meta‐Analysis

Abstract: Objectives/Hypothesis: To determine the rate and predictors of receiving multiple tympanostomy tube (TT) placements in children.Study Design: Systematic review and meta-analysis. Methods: PubMed, EMBASE, and Cochrane Library databases were searched for studies reporting the risk factors for receiving repeat TT (r-TT) placements in children with chronic otitis media with effusion or recurrent acute otitis media. These articles were systematically reviewed in accordance with the Preferred Reporting Items for Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…About 25% of children will need a second set of short‐term tympanostomy tubes, and about 8% require a third set 201 . Risk factors associated with repeat tube placement, as determined by systematic review of the literature, include craniofacial disease and shorter retention time (eg, early extrusion) of the first set of ear tubes 201 .…”
Section: Guideline Key Action Statementsmentioning
confidence: 99%
See 2 more Smart Citations
“…About 25% of children will need a second set of short‐term tympanostomy tubes, and about 8% require a third set 201 . Risk factors associated with repeat tube placement, as determined by systematic review of the literature, include craniofacial disease and shorter retention time (eg, early extrusion) of the first set of ear tubes 201 .…”
Section: Guideline Key Action Statementsmentioning
confidence: 99%
“…201 Risk factors associated with repeat tube placement, as determined by systematic review of the literature, include craniofacial disease and shorter retention time (eg, early extrusion) of the first set of ear tubes. 201 Additional risk factors for repeat tympanostomy tube surgery, identified by other studies, include having a parent who is a smoker, daycare attendance, breastfeeding for under 3 months, pacifier use, tympanic membrane atelectasis, male sex, asthma, gastrointestinal disease, prematurity, and age. [205][206][207] With numerous risk factors identified from observational studies of varying risk of bias, it is difficult to predict which child would benefit from a longer duration of middle ear ventilation.…”
Section: Action Statement Profilementioning
confidence: 99%
See 1 more Smart Citation
“…5,6 Adenoidectomy can greatly improve the remission rate of OME, and adenoidectomy along with tympanotomy tube insertion can simultaneously reduce the repeated grommet insertion rate in children with OME. 7,8 Currently, there have been only a few relevant studies and conclusions regarding whether severe hypoxia during sleep occurs in children with OME. Braun et al found that there was no difference in the apneahypopnea index (AHI), apnea index (AI), hypopnea index (HI), snoring index, or nocturnal lowest oxygen saturation (LSaO 2 ) between children with OME and the control group.…”
Section: Introductionmentioning
confidence: 99%
“… 5 , 6 Adenoidectomy can greatly improve the remission rate of OME, and adenoidectomy along with tympanotomy tube insertion can simultaneously reduce the repeated grommet insertion rate in children with OME. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%